Raising Awareness of Climate Change: Nature, Activists, Politicians? - Daryna Grechyna (Center for Economic Studies and ifo Institute (CESifo), 2024)
This paper evaluates the relative importance of natural and human factors in shaping public awareness of climate change. I compare the predictive efficacy of natural factors, represented by air temperature deviations from historical norms, and human factors, encompassing noteworthy political events focused on environmental policies and movements led by environmental activists, in forecasting the salience of climate change topic over weekly and annual horizons using regional European countries' data. The salience of climate change is proxied by the Google search intensity data. The activists' movements are measured by weekly Friday for Future strikes. The best-performing predictor in the short term (weeks), is the size of activists' strikes and in the longer term (years), positive deviations of maximum air temperature from historical norms and political meetings focused on environmental policies. The inter-regional spatial relations, when taken into account, significantly improve the forecasts of the future public interest in climate change.
Keywords: Q01; Q52; Q58; C33; 330; climate change; activists' strikes; political meetings; weather